A Modified Organic Method for Preparation of Ibuprofen Microcapsules As a Sustained Release Solid Dosage Form - Issraa Rasheed Abed Al- Rahman; Alaa A. A.Rasool; Fatima A. Tawfiq (College of Pharmacy University of Baghdad, 2017)
ABSTRACT: Microencapsulation is used to modify and retard drug release as well as to overcome the unpleasant effect (gastrointestinal disturbances) which are associated with repeated and overdose of ibuprofen per day. So that, a newly developed method of microencapsulation was utilized (a modified organic method) through a modification of aqueous colloidal polymer dispersion method using ethylcellulose and sodium alginate coating materials to prepare a sustained release ibuprofen microcapsules. The effect of core : wall ratio on the percent yield and encapsulation efficiency of prepared microcapsules was low, whereas , the release of drug from prepared microcapsules was affected by core: wall ratio ,proportion of coating material and presence of additive(PEG4000). The 2:1 core : wall ratio was compared (in weight equivalent to 300mg and 600mg drug) with Fenbid® spansule capsule 300mg and Balkaprofen® tablet 600mg respectively. It was found that the release of drug from selected ratio and Balkaprofen® tablet was more or less similar(P 0.05) .This sustained release ratio was encapsulated in weight equivalent to 300mg drug to be administered once daily (600mg) as two capsules as the reference. The capsules were stable within 6 months of storage at room temperature.